Mile-High Multiculturalism. - Hillerman, Tony (Smithsonian, 2006)
The article presents author Tony Hillerman's opinions on the town he lives in Los Ranchos De Albuquerque, New Mexico. Hillerman discusses the bosque, which is the longest strip of unbroken woodland in North America. Los Ranchos De Albuquerque is four miles wide and has a population of around five thousand. According to the United States Postal Service, the town is officially part of Albuquerque, New Mexico. The history of the town is discussed, as well as a discussion about water rights that are unique to the town since the time of the Mexican-American War. Hillerman also discusses the many Native America populations that he feels make the town interesting.